2022
DOI: 10.1177/15353702221081027
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal intronic RNA-Seq analysis of Parkinson’s disease patients reveals disease-specific nascent transcription

Abstract: Transcriptomic studies usually focus on either gene or exon-based annotations, and only limited experiments have reported changes in reads mapping to introns. The analysis of intronic reads allows the detection of nascent transcription that is not influenced by steady-state RNA levels and provides information on actively transcribed genes. Here, we describe substantial intronic transcriptional changes in Parkinson’s disease (PD) patients compared to healthy controls (CO) at two different timepoints; at the tim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The PPMI data set used in this study included controls without PD, and cases with confirmed PD, prodromal PD and scan without evidence of dopaminergic deficit (SWEDD) PD. The RNA-sequencing of the PPMI data set has been outlined elsewhere, 8,9 and a summary of the individuals included in this study at each time point is given in Table 1. Consent from all the study participants was previously obtained by the PPMI and conformed with the ethical standards of the World Medical Association Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…The PPMI data set used in this study included controls without PD, and cases with confirmed PD, prodromal PD and scan without evidence of dopaminergic deficit (SWEDD) PD. The RNA-sequencing of the PPMI data set has been outlined elsewhere, 8,9 and a summary of the individuals included in this study at each time point is given in Table 1. Consent from all the study participants was previously obtained by the PPMI and conformed with the ethical standards of the World Medical Association Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…Substantial intronic transcriptional changes in PD patients compared to healthy controls have been reported [70]. Although the exact cause of PD is unknown, several factors, such as genetic, environmental, and head trauma, are implicated in the disease process.…”
Section: Lewy Bodies Are a Key Characteristic Of Pdmentioning
confidence: 99%
“…Although the exact cause of PD is unknown, several factors, such as genetic, environmental, and head trauma, are implicated in the disease process. Mutations in certain genes, such as SNCA, PARK2, PARK7, PINK1, and LRRK2, can lead to the development of PD [20,[70][71][72][73]. The onset of neurodegenerative diseases may be influenced by a combination of environmental and genetic factors, including interactions between genes.…”
Section: Lewy Bodies Are a Key Characteristic Of Pdmentioning
confidence: 99%
“…miRNA analysis from the blood and brains from PD subjects revealed known and novel biomarkers implicated in PD development and progression, such as axon guidance, TGF-β signaling pathway, ubiquitin-mediated proteolysis, and endocytosis [ 61 ]. Besides miRNA changes in PD-associated tissues, highly specific time-dependent intronic transcriptional changes were observed in blood RNA-seq but not yet tested in the brain [ 62 ].…”
Section: Neurodegeneration: Parkinson’s and Alzheimer’s Diseasesmentioning
confidence: 99%